Low-Impact Design for Environmental Resilience: Exploring the Role of Materials and Infrastructure in Sustainable Development - Saripuddin M; Grace Williams; Josephine Kamara (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Environmental degradation and climate change pose significant challenges to sustainable development, particularly in urban infrastructure and built environments. Conventional construction practices contribute to resource depletion, greenhouse gas emissions, and ecosystem disruption, necessitating innovative approaches that enhance environmental resilience. Low-impact design strategies, emphasizing sustainable materials and resilient infrastructure, offer potential pathways to reduce environmental footprints while supporting long-term societal and ecological sustainability. Purpose. This study aims to examine the role of materials and infrastructure in promoting environmental resilience through low-impact design. Specific objectives include assessing the effectiveness of sustainable construction materials, evaluating design strategies that mitigate environmental impacts, and identifying practical solutions for integrating resilience principles into urban development. Method. A mixed-methods research design was employed, combining quantitative life-cycle assessment (LCA) of material and infrastructure impacts with qualitative case studies of sustainable projects across urban settings. Data analysis focused on material performance, energy efficiency, waste reduction, and adaptation to climate-related stressors. Results. Findings indicate that low-impact materials and resilient infrastructure can substantially reduce carbon emissions, energy consumption, and environmental degradation while enhancing adaptive capacity to climate variability. Case studies demonstrate measurable improvements in both ecological and social outcomes when resilience principles are embedded in design and construction practices. Conclusion. The study concludes that low-impact design is a critical enabler of sustainable development, offering evidence-based guidance for architects, engineers, and policymakers to foster environmentally resilient infrastructure.